How financial education contributes to the autonomy and fulfillment of young Brazilians - Becker, Júlia (2024)
Ineffective management of young people's personal finances can lead to many personal and social conflicts, including difficult relationships between members of society. Many people see society only as a consumer, so it becomes necessary to manage their personal finances to avoid greater losses. In this sense, this study sought to understand how young people are currently relating to their own finances. Therefore, the objective of this study was to verify how financial education contributes to building the financial autonomy of young Brazilians. To build its theoretical basis, a bibliographical survey was carried out, based on an integrative literature review. From this, analyzes were constructed using the following criteria: theme, objectives, contributions, conclusions and main limitations defined based on the scope of the research. With the result obtained, it was possible to verify the trends in research related to financial education in Brazil, in which the sample of articles revealed significant differences between men and women in terms of age, education level, income and marital status, levels of confidence and aversion. the lost. Knowledge of financial education aims to understand how knowledge of financial education can contribute to the training of elementary school students. How the relationship between the media and the subject interferes with their consumerism so that they know how to evaluate the best options for purchasing products in promotions so as not to end up falling into behavioral influences. Finally, the contributions left by the publications used. In conclusion, the relevance of the topic is highlighted in the context presented and, for the continuation of the research, it is also recommended that an in-depth study be carried out on the topic of financial education. In addition, carry out a practical application and a new research approach so that it is possible to further visualize the behavioral bias of young people.